2009
DOI: 10.1111/j.1460-9568.2009.06697.x
|View full text |Cite
|
Sign up to set email alerts
|

The dorsomedial hypothalamic nucleus is not necessary for food‐anticipatory circadian rhythms of behavior, temperature or clock gene expression in mice

Abstract: Circadian rhythms in mammals are regulated by a light-entrainable circadian pacemaker in the hypothalamic suprachiasmatic nucleus and food-entrainable oscillators located elsewhere in the brain and body. The dorsomedial hypothalamic nucleus (DMH) has been proposed to be the site of oscillators driving food-anticipatory circadian rhythms, but this is controversial. To further evaluate this hypothesis, we measured clock gene, temperature and activity rhythms in intact and DMH-ablated mice. A single 4-h midday fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 54 publications
7
121
0
3
Order By: Relevance
“…As mentioned in the Introduction, however, food-anticipatory components can be reduced after lesions of the parabrachial nucleus (Davidson et al, 2000), the core of the accumbens nucleus (Mendoza et al, 2005b) and possibly the dorsomedial hypothalamus (Gooley et al, 2006). The role of this hypothalamic region in food anticipation, however, remains highly controversial (Landry et al, 2006;Mistlberger et al, 2009;Moriya et al, 2009). This relative paucity of positive findings despite extensive research has led to the hypothesis that the food-entrainable oscillator may actually not be localized in a particular brain region but instead, may involve a distributed cerebral network resulting from interactions of a set of brain regions directly sensitive or not to metabolic cues coming from peripheral organs (Mistlberger, 1994;Stephan, 2001;Mendoza, 2007).…”
Section: Food Anticipation Is Attenuated or Lacking In Mice With Cerementioning
confidence: 99%
“…As mentioned in the Introduction, however, food-anticipatory components can be reduced after lesions of the parabrachial nucleus (Davidson et al, 2000), the core of the accumbens nucleus (Mendoza et al, 2005b) and possibly the dorsomedial hypothalamus (Gooley et al, 2006). The role of this hypothalamic region in food anticipation, however, remains highly controversial (Landry et al, 2006;Mistlberger et al, 2009;Moriya et al, 2009). This relative paucity of positive findings despite extensive research has led to the hypothesis that the food-entrainable oscillator may actually not be localized in a particular brain region but instead, may involve a distributed cerebral network resulting from interactions of a set of brain regions directly sensitive or not to metabolic cues coming from peripheral organs (Mistlberger, 1994;Stephan, 2001;Mendoza, 2007).…”
Section: Food Anticipation Is Attenuated or Lacking In Mice With Cerementioning
confidence: 99%
“…Previous studies demonstrated that RF entrains and shifts the circadian expression of clock genes in several non-SCN regions of the brain and peripheral tissues, whereas rhythmicity in the SCN remains phase-locked to the external light/dark cycle (Damiola et al, 2000;Stokkan et al, 2001;Wakamatsu et al, 2001;Mieda et al, 2006;Moriya et al, 2009). Thus, we next studied Per1 and Per2 mRNA expression rhythms entrained by feeding in several brain regions of N-Bmal1 Ϫ/ Ϫ and control mice using in situ hybridization.…”
Section: N-bmal1mentioning
confidence: 99%
“…The differential effects of both lesion strategies may explain why such controversy in the literature exists concerning the effect of the lesion of the DMH with respect to FAA (25,26). In general, it can be stated that in studies demonstrating little or no diminishment on FAA after lesions of the DMH, the lesions encompassed the DMH completely, as well as parts of neighboring structures, thus often resulting in nearly arrhythmic animals (6,7,25). This loss of rhythmicity suggests that with such large lesions, the SCN is unable to impose its rhythmicity to areas such as the perifornical area, the ventro lateral hypothalamus, and the thalamus (27,28).…”
mentioning
confidence: 99%
“…The designation of the DMH as master clock for food entrainment is, however, controversial because some groups reported unimpaired FAA despite large lesions of the DMH (6, 7); others have shown that lesions of the DMH disturb and diminish the intensity of FAA (6). The possible participation of other brain structures in FAA is evident from studies that demonstrate modulation of neuronal activity and induction of clock-gene rhythmicity in hypothalamic and limbic structures by feeding schedules (8)(9)(10)(11).…”
mentioning
confidence: 99%